2014
DOI: 10.1007/s13197-014-1639-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics studies with fruit bromelain (Ananas comosus) in the presence of cysteine and divalent ions

Abstract: The kinetics of cysteine and divalent ion modulation viz. Ca 2+ , Cu 2+, Hg 2+ of fruit bromelain (EC 3.4.22.33) have been investigated in the present study. Kinetic studies revealed that at pH 4.5, cysteine induced V-type activation of bromelain catalyzed gelatin hydrolysis. At pH 3.5, Ca 2+ inhibited the enzyme noncompetitively, whereas, both K-and V-type activations of bromelain were observed in the presence of 0.5 mM Ca 2+ at pH 4.5 and 7.5. Bromelain was inhibited competitively at 0.6 mM Cu 2+ ions at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Fruit bromelain extracted from Perola pineapple species have its highest activity at pH 7, and it also showed another two minor activity peaks at pH 4.5 and 8.5 (Ferreira, Santana, & Tambourgi, ). As research on papain suggested that fruit cysteine proteases conduct their catalysis through ionizable groups, and the ionic form of their active sites impacts the pH preference (Kaur, Kaur, & Grewal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fruit bromelain extracted from Perola pineapple species have its highest activity at pH 7, and it also showed another two minor activity peaks at pH 4.5 and 8.5 (Ferreira, Santana, & Tambourgi, ). As research on papain suggested that fruit cysteine proteases conduct their catalysis through ionizable groups, and the ionic form of their active sites impacts the pH preference (Kaur, Kaur, & Grewal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bromelain has a wide specificity for protein cleavage and is stable over a broad pH range (pH 4-8). It generally cleaves the protein sites with arginine, lysine, tyrosine, glutamic acid, glycine, ornithine, methionine sulfoxide, and alanine, but the specificity of cleavage may be altered by a change in pH [23,24]. Trypsin hydrolyses C-terminal amide bond specifically to arginine and lysine.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit bromelain (FB) is a type of protease enzymes found in pineapple that has widely accepted as a phyto-therapeutic drug (Kaur, Kaur, & Grewal, 2015;Ramli, Abdul Manas, Abdul Hamid, Abd. Hamid, & Md Illias, 2018).…”
Section: Introductionmentioning
confidence: 99%